А Computer Simulation of Radiation-Induced Structural Changes and Properties of Multiperiod ZrNx/MoNx System - O.V. Sobol'; A.A. Meylekhov; T.V. Bochulia; V.A. Stolbovoy; V.F. Gorban'; А.А. Postelnyk; S.M. Shevchenko; A.V. Yanchev (Журнал нано- та електронної фізики)
Influence of the period value Λ (at different negative potential Ub that supplied during deposition) on phase composition, structure, stress-strain state and hardness of multiperiod coatings ZrNx/MoNx is investigated by using complex methods of validation structural state at combined with microindentation. Formation in layers ZrNx and MoNx the phases with cubic lattice and preferred orientation of crystallites with axis [100] is established. Stress-strain state of compression with increasing Ub is amplified and reaches maximum value (– 6.7 GPa) at Λ  20 nm and Ub  – 110 V. Hardness of coating increases with decreasing Λ from 300 to 20 nm. Coatings that obtained with Λ  20 nm and Ub  – 110 V have the highest hardness 44 GPa. Relaxation of structural compressive stresses and decreasing hardness is happening at smaller Λ and larger Ub  – 110 V (as a result of radiation-stimulated forming defect and mixing). Data of computer modeling of defectiveness at atomic level at bombardment of ions that accelerated in field Ub are used to explain the results.